Analysis of the Textbook "Aku Cinta Bahasa Arab" for Grade 1 Elementary School in the Perspective of Cognitive Developmental Psychology - Dudung Hamdun; Rafika Rizkinia Mufida; Nurhapsari Pradnya Paramita (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to determine the feasibility of the textbook "Aku Cinta Bahasa Arab" for grade 1 elementary school published by Tiga Serangkai in terms of the psychology of children's cognitive development. This research is library research with content analysis method. The data collection technique in this research is documentation. Sources of data used in this study are books, journals, documents, articles, and other scientific works relevant to the study's object of study. The main topics of this research are theories related to textbook assessment and cognitive development of elementary-age children. The data collection technique in this research is documentation. Furthermore, to process and analyze the data, the author uses the method of content analysis, which is an analysis of the content that focuses on interpretation in terms of assessing the feasibility of textbooks and reviewing theories of cognitive development for elementary-age children. The results of this study indicate that there is a suitability of the assessment of texts with children's cognitive development. However, there are still errors both in terms of technique and substance of the book. Various improvements are needed to be used as learning materials in accordance with the cognitive development of children in the grade 1 elementary school. Keywords: Textbooks, Aku Cinta Bahasa Arab, Content Analysis, Cognitive Development. Abstrak Penelitian ini bertujuan untuk mengetahui kelayakan buku teks “Aku Cinta Bahasa Arab” untuk Kelas I Madrasah Ibtidaiah yang diterbitkan oleh Tiga Serangkai ditinjau dengan psikologi perkembangan kognitif anak. Penelitian ini merupakan penelitian pustaka (library research) dengan metode analisis konten. Teknik pengumpulam data pada penelitian ini adalah dokumentasi. Sumber data yang digunakan dalam penelitian ini yaitu buku, jurnal, dokumen, artikel, dan karya ilmiah lainnya yang relevan dengan objek kajian pada penelitian ini. Pokok bahasan dalam penelitian ini yaitu teori-teori yang berkaitan dengan penilaian buku teks dan perkembangan kognitif anak usia dasar. Teknik pengumpulam data pada penelitian ini adalah dokumentasi. Selanjutnya, untuk mengolah dan menganalisis data, penulis menggunakan metode content analysis, yaitu analisis terhadap kandungan isi yang berfokus pada interpretasi dari segi penilaian kelayakan buku teks dan ditinjau teori-teori perkembangan kognitif anak usia dasar. Hasil penelitian ini menunjukkan bahwa terdapat kesesuaian penilaian buku teks dengan perkembangan kognitif anak, namun masih terdapat kesalahan baik dari sisi teknik maupun substansi buku, dan diperlukan berbagai upaya perbaikan supaya dapat dijadikan bahan belajar yang sesuai dengan perkembangan kognitif anak pada usia kelas satu sekolah dasar. Kata Kunci: Buku Teks, Aku Cinta Bahasa Arab, Analisis Konten, Perkembangan Kognitif